PENGARUH ELECTRONIC WORD OF MOUTH (eWOM) DAN CITRA MEREK TERHADAP MINAT BELI PRODUK PERAWATAN WAJAH BERBAHAN HERBAL - Pangaribuan, Dinda Aulia Sari; Aprilia, Anisa; Wahyuningtyas, Agustina Shinta Hartati (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
When someone gets information in the form of review valence and they feel that the review influences them, review helpfulness can be formed, and the brand image that product X already has will influence trust in business actors, which can ultimately lead to purchase intention. The aim of this reasearch is to analyze the influence of review valence on review helpfulness, review valence on purchase intention X herbal skincare products, review helpfulness on purchase intention X herbal skincare products, and the influence of brand image in moderating the indirect relationship between review valence and purchase intention through review helpfulness. The research was carried out via Instagram, TikTok and X (Twitter) social media accounts from November to December 2023. The total sample was 60 students who carried out by non-probability sampling using purposive sampling technique. Data was collected by distributing online questionnaires, then analyzed using SEM-PLS with SmartPLS software. The research results show that review valence has a positive and significant effect on review helpfulness, review valence has a positive and significant effect on purchase intention, review helpfulness has a positive and significant effect on purchase intention, and high brand image has a positive but not significant effect, thereby reducing the strength of the relationship between review valence on purchase intention through review helpfulness. The R-Square value shows 0.20, which means that the review valence and review helpfulness variables influence consumer purchase intention by 20% and the rest through other non-model variables.